Islamic Capital Market Reaction on Presidential Election 2019 (Case Study of the Jakarta Islamic Index) - Utami, Syintia Dwi; Qoyum, Abdul (Universitas Ahmad Dahlan, 2020)
General Election (GE) is one of the most important political issues which has an impact on the economic condition. This research aims to reveal the effect of General Election 2019 on the capital market reaction. Specifically, the study compares the impact of three events in the GE 2019, namely, The General Election 2019, the announcement of Elected President 2019, and Mahkamah Konstitusi (MK) decision. By employing Abnormal Return with t-test analysis, the study reveals that the publication of the elected-president has the most significant impact on the Islamic Capital Market compares to the two other events. While using Trading Volume Activity (TVA), all the three events of GE 2019 affects the TVA. This finding suggests that for the Islamic capital market investor, the announcement of the elected president is seen as the most significant event that determines the whole of economic condition for the next five years. Hence, for the policy-makers, they must focus on the date of the announcement by preparing such a policy to maintain the market condition.Â Â Â